PLASTIC PACKAGING WASTE MANAGEMENT THROUGH FILLING MACHINE WITH AGILE REENGINEERING PROJECT MANAGEMENT APPROACH - Patricia, Gracella; Muslim, Erlinda (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2023)
In Indonesia, the number of plastic wastes has reached 66 million tons per year in which 50% of them come from plastic packaging waste. Meanwhile, the recycling of plastic packaging waste only reaches 14%. Hence, it is highly urgent to be aware of plastic packaging waste management in order to tackle this issue. The research discussed the capability and potential of applying digitalization and automation to Smart Retail Technology which focuses on filling machines to manage plastic packaging waste management and increase the competitive advantage. This research uses two main approaches, namely Business Process Reengineering and Agile Project Management to recommend a new business process on ongoing project. The result of the study suggests the urgency to take advantage of the QR Code and Human Machine Interface to maximize the effectiveness and results of implementing the business process. By using simulation, this effort is expected to reach up to 334 consumers each day with up to 42.14% of machine utilization.